Kekerasan Komunikasi Verbal Orang Tua Terhadap Anak di Desa Kebun Kelapa Kabupaten Langkat - Fadilah, Rizky (KESKAP: Jurnal Kesejahteraan Sosial, Komunikasi dan Administrasi Publik, 2024)
Verbal violence or verbal abuse is part of the act of communication using harsh words or words or verbal violence carried out by parents on children. Indonesian children experience violence in environments that should be safe because they are with people they should be able to trust. However, data shows that Indonesian children are exposed to both psychological aggression and physical punishment at home. This research aims to analyze the phenomenon of verbal communication violence perpetrated by parents against children. This research uses a qualitative research method with a case study approach. The data collection process was obtained from observations and interviews with informants. The analysis technique used is a qualitative data analysis technique which consists of data reduction, data presentation and drawing conclusions. The results of research conducted on several sources found that verbal communication violence by parents towards children often occurs. The main trigger expressed by most interviewees was the parents' desire to discipline their children and ensure that their children obeyed their orders or prohibitions. Several sources stated that when the communication used is "normal" or not firm, children tend to ignore commands. In an effort to discipline their children, parents feel the need to use harsher, even harsh language, in the hope that the child will feel afraid and be more obedient.